Cortical Inhibition State-Dependent iTBS Induced Neural Plasticity - Diao, Xiaoying; Lu, Qian; Qiao, Lei; Gong, Youhui; Lu, Xiao; Feng, Min; Su, Panpan; Shen, Ying; Yuan, Ti-Fei; He, Chuan (Frontiers in Neuroscience, 2022)
Background: Intermittent theta burst stimulation (iTBS) is an effective stimulus for LTP-like plasticity. However, iTBS-induced effects varied greatly between individuals. Ample evidence suggested that an initial decrease in local γ-aminobutyric acid (GABA) or enhancement in N-methyl-D-aspartate (NMDA) facilitation neurotransmission is of vital importance for allowing LTP-like plasticity to occur. Therefore, we aimed to investigate whether the individual level of GABA or NMDA receptor-mediated activity before stimulation are correlated to the after-effect in cortical excitability induced by iTBS. Methods: Fifteen healthy volunteers were recruited for the present study. We measured SICI, LICI and ICF, which index GABAA receptor-, GABAB receptor-, and glutamate receptor-mediated activity respectively in cortex before conducting iTBS. After iTBS intervention, the changes of motor evoked potentials (MEPs) amplitude were taken as a measure for cortical excitability in response to iTBS protocol. Results: There was a significant negative correlation between the amount of SICI measured before iTBS and the after-effect of iTBS-induced LTP-like plasticity at the time point of 5 min, 10 min and 15 min after inducing iTBS. Multiple linear regression model indicated that SICI was a good predictor of the after-effect in cortical excitability induced by iTBS at 5, 10 and 15 min following stimulation. Conclusions: The present study found that GABAA receptor-mediated activity measured before stimulation is negatively correlated with after-effect of cortical excitability induced by iTBS. SICI, as index of GABAA receptor-mediated activity measured before stimulation might be a good predictor of iTBS-induced LTP-like plasticity for a lasting of 15 min following stimulation. Keywords: intermittent theta burst stimulation; LTP-like plasticity; GABAA receptor-mediated activity; GABAB receptor-mediated activity; N-methyl-D-aspartate receptor-mediated activity.